Herpetofauna Diversity and Taxa Richness Ground Cover Plant as Bioindicator Environmental Quality in Boon Pring at Sanankerto, Turen, Malang Regency - Anggarwanto, Wahyu; Arisoesilaningsih, Endang (Journal of Indonesian Tourism and Development Studies, 2019)
Boon Pring is one of the ecotourism destinations in Malang regency with tourism attractions including motor boats, water bikes, and picnic activities. These activities can cause environmental degradation in Boon Pring area. The purpose of this research is to analyze taxa richness of ground cover plant, diversity, and community structure of herpetofauna in Boon Pring and explain the environmental quality in Boon Pring based on their relationship. The method used is selective purposive belt transect with 10 m long belt and 10x5 m2 plot area. Each station is repeated four times. The data obtained were analyzed with Ms. Excel and the PAST program to search Taxa Richness for plants, abundance, frequency, Shannon - Wiener diversity index and Import Value Index (IVI) for Herpetofauna. Then they were analyzed regression, cluster, and biplot to determine the relationship between the two. The results showed decreased of ground cover plants taxa richness and herpetofauna diversity index from station one to station four. The value of IVI indicates the dominance of Eutrophis multifasciuata species in degraded sites. Determination coefficient showed a value of 51%, which means there is a positive relationship between ground cover plant and herpetofauna diversity. The conclusions of this study, the taxa richness of ground cover and diversity of herpetofauna have decreased in areas with degraded environmental quality. There is a dominance of one type of herpetofauna in the degraded areas of Eutrophis multifasciuata. Between the taxa richness of ground cover plants and diversity of herpetofauna showed a positive relationship, in this study 51%. Keywords: Boon Pring, Diversity Index, Ground Cover Plant, Herpetofauna, Regression.